Exhaust gas after treatment using air preheating and selective catalytic reduction by urea to reduce NOx in diesel engine - Mohammad Shahed H.K. Tushar; Musa Ibne Mannan; Afra Azmain (Heliyon)
The oxides of nitrogen (NOx) emitted from diesel engines are perilous pollutants, contributing to environmental and health hazards. Selective Catalytic Reduction (SCR) using urea is a proven technology for reducing NOx emissions, while air preheating has been utilized to enhance NOx reduction efficiency. From the studies, a sole focus on urea-SCR with air preheating remains noticeably unexplored. This study presents an integrated approach using urea-SCR and air preheating in a four-stroke, single-cylinder, water-cooled diesel engine for a comparative study in decreasing NOx emissions. The experimental setup involved a mechanical urea injection system, a platinum-rhodium catalyst, and an air-preheating mechanism utilizing exhaust gas heat. Tests were conducted at varying engine speeds and loads to evaluate the combined system's performance. Results indicate that the combined air preheating and urea-SCR system achieved a NOx reduction of up to 55 % under low engine load conditions, with a corresponding CO emission reduction of 19 % for preheated set-up. The system enhanced brake thermal efficiency (BTE) and reduced brake-specific fuel consumption (BSFC) compared to baseline configurations, with no significant backpressure observed. A significant noise level reduction (21–27 %) was also achieved, highlighting the dual benefits of emissions and noise control. The findings demonstrate that combining urea-SCR with air preheating is an effective strategy for reducing NOx emissions while maintaining or improving engine performance. This approach offers a promising pathway for enhancing diesel engine emission control systems. Further studies are recommended to explore the scalability of this method for larger engines and to assess long-term system stability.